Dynamic Simulation Research of Hydro-Mechanical CVT. Issue 1 (2nd January 2022) - Xiao, Maohua; Wang, Yuewen; Zou, Fan; Zhang, Haijun; Li, Xianhua
Abstract : In order to study the complex dynamic characteristics of hydro-mechanical CVT (hydro-mechanical continuously variable transmission), the gearbox machine dynamics simulation model based on AMESim was established for the most important of confluent planetary gear mechanism in the gearbox. Creo2.0 was used to draw 3D virtual prototype, and according to the actual movement of the link, added the corresponding constraints to get the planetary dynamics simulation model based on the multi-body dynamics simulation software ADAMS. Based on the classical formula of gear meshing force, the theoretical values of meshing force of planetary gear were calculated, and the dynamics analysis of planetary gear was carried out by using ADAMS. The simulation results were basically consistent with the theoretical values. It researched the influence of the speed regulation process on planetary gear engagement impact under the three case: speed regulation rate and speed direction, speed regulation under different load levels and different engine speed. The speed regulation under speed regulation rate and different load levels had obvious impact on planetary gear meshing force, the impact degree increased with the increasing of speed regulation rate and load; this work has good engineering and application value, and provides the reference for the structure optimization and adjustment.